Study on the Current Situation and Countermeasures of Undertaking Industrial Transfer in Western China - Hongyu Zhi, Cao Bing (Forest Chemicals Review)
Industrial transfer has become a major trend of contemporary world economic development. China’s industrial transfer is gradually developed from the eastern coastal agglomeration to the central and western regions. The cost of factors in the east keeps rising, while the western region is in the early stage of development, rich in natural resources, low cost of factors of production and large market potential, which will inevitably become an important bargaining chip for the western region to attract the industrial transfer of developed regions. Under such background, this paper analyzes the current situation of undertaking industrial transfer in western China from the aspects of scale, source of industry, level of industry, mode of industry transfer and construction of demonstration area of industry transfer. Through literature analysis and data analysis, it is found that in the process of undertaking industrial transfer in western China, the ecological environment has been destroyed, the state of "high growth, low development", the acceleration of disorderly competition, and the passive economic growth. Based on this, this paper also puts forward a series of corresponding countermeasures to these problems, in order to promote the western regions to undertake high-quality industrial transfer for reference.